Pengaruh Rata-Rata Lama Sekolah Kabupaten/Kota Terhadap Persentase Penduduk Miskin Kabupaten/Kota di Provinsi Jawa Timur Tahun 2017 - Abdul Hadi (Trunojoyo University of Madura, 2019)
The way a person thinks in dealing with a problem is greatly influenced by the knowledge of the person. The main foundation of knowledge is through education. With the high level of education, there are more choices for people to live more prosperously. measure the magnitude and direction of the relationship between the average length of school, residence, and the percentage of the poor, (2) measure the magnitude of the influence of the average length of school, residence of the population on the percentage of poor people. This research method uses statistical Pearson correlation and linear regression. this study shows a strong negative relationship between the average length of school and the percentage of poor people. This very strong negative relationship explains that the higher the average school year, the lower the percentage of poor people. In addition to being strongly related, the average length of school also significantly affects the percentage of poor people. However, other factors need to be sought that can reduce the percentage of poor people more quickly.